Detecting Articular Cartilage and Meniscus Deformation Effects Using Magnetization Transfer Ultrashort Echo Time (MT-UTE) Modeling during Mechanical Load Application: Ex Vivo Feasibility Study. (December 2021) - Jerban, Saeed; Kasibhatla, Akhil; Ma, Yajun; Wu, Mei; Chen, Yanjun; Guo, Tan; Wan, Lidi; Szeverenyi, Nikolaus; Chang, Eric Y.; Du, Jiang
Objective: Ultrashort echo time (UTE) magnetic resonance imaging (MRI) sequences have improved imaging of short T2 musculoskeletal (MSK) tissues. UTE-MRI combined with magnetization transfer modeling (UTE-MT) has demonstrated robust assessment of MSK tissues. This study aimed to investigate the variation of UTE-MT measures under mechanical loading in tibiofemoral cartilage and meniscus of cadaveric knee joints. Design: Fourteen knee joints from young ( n = 8, 42 ± 12 years old) and elderly ( n = 6, 89 ± 4 years old) donors were scanned on a 3-T scanner under 3 loading conditions: load = 300 N (Load1), load = 500 N (Load2), and load = 0 N (Unload). UTE-MT sequences were performed at each loading condition. Macromolecular proton fraction (MMF) was calculated from UTE-MT modeling. Wilcoxon rank sum test was used to examine the MRI data differences between loading conditions. Results: For young donors, MMF increased in all grouped regions of interest (meniscus [M], femoral articular cartilage [FAC], tibial articular cartilage [TAC], articular cartilage regions covered by meniscus [AC-MC], and articular cartilage regions uncovered by meniscus [AC-UC]) when the load increased from 300 to 500 N. The increases in MMF were significant for M (13.3%, P < 0.01) and AC-MC (9.2%, P = 0.04). MMF decreased in all studied regions after unloading, which was significant only for AC-MC (−8.9%, P = 0.01). For elderly donors, MRI parameters did not show significant changes by loading or unloading. Conclusion: This study highlights the potential of the UTE-MT modeling combined with knee loading in differentiating between normal and abnormal knees. Average tissue deformation effects were likely higher and more uniformly distributed in the joints of young donors compared with elderly donors.